The Term Structure with Semi‐credible Targeting - Farnsworth, Heber; Bass, Richard (Journal of Finance, 2003)
ABSTRACT The Federal Reserve sets targets for interest rates which it enforces through direct market intervention. These targets are changed periodically. In this paper, we develop a term structure model in which the short rate is subject to a control which keeps it close to a target which changes from time to time. The probability of target changes is not constant in the model, but changes as a function of observables. The model performs well at explaining the shifts in the yield curve that accompany target changes.